ANALISIS KANDUNGAN PHOSPAT (PO4) DAN NITRAT (NO3) DI SUNGAI KARANG MUMUS SAMARINDA - Vita Pramaningsih; Slamet Suprayogi; Ig. L. Setyawan Purnama (EnviroScienteae, 2017)
Estuary of Karang Mumus River is Mahakam River that used for drinking water substance in around Samarinda Province East Kalimantan. There are communities live along floodplain area and use water in the river for daily activities as the bath, washing, and privy. Karang Mumus River through the urban area with complicated activities. Domestic waste content in Karang Mumus River come from the communities activities. It content nutrition as Phosphate and Nitrate reason booming algae in the tributary. It happens to impact the water pollution since less Dissolved Oxygen (DO). Purpose this research is analysis distribution of Phosphate and Nitrate in Karang Mumus River. The method used surveys as observation, water sampling, and laboratory analysis. Measurement spot is 17 from upstream to downstream. The result Nitrate is excellent but Phospat high on some spot measurement. Especially it happens in part of urban, market and several communities. The highest Nitrate is 2.13 mg/L standard 10 mg/L and highest Phosphate is 0.86 mg/L standard 0.2 mg/L.